"Primitive Realities" and the "Meta-Translatability of Language" in the Poetry of Alexandre Amprimoz. Issue 2 (July 2019) - Viselli, Antonio
Abstract : The poetry of Alexandre Amprimoz (1948–2012), Italian-born Franco-Canadian poet and critic, explores how poetry signifies as well as its creative-destructive impulse. His writing serves as a bridge, albeit postmodernly a posteriori, between Symbolist and modernist poetics in French, English, Italian and Spanish. This article unpacks the poet's conceptions of "primitive realities" and "meta-translation" with a focus on the intermediality of musico-literary fugue and the intertextual references to Ezra Pound's The Cantos . Counterpoint, the fundamental polyphonic quality of fugue, can only be suggested in literature, given the linear nature of text and the referentiality of language. Through musical references and via musical characteristics applied to poetry, Amprimoz explores a contradictory creative-destructive dynamism in his writing: one must dismantle linguistic meaning in order to create a new poetic form. Through the evocation of music, an amimetic art form which differs from the semiotics of language, the poet accomplishes this task at least in part, thus accessing the primitive realities to which he alludes (the pre-literate or child-like world) through the development of meta-translation (translating the very process of translation, as well as its impossibility). The primary texts explored in this study include Vers ce logocentre (1978) and In Rome (1980).